Biaya Satuan dan Pemulihan Biaya (Cost Recovery Rate) Layanan Pasien Acute Coronary Syndrome dengan Rawat Inap di Rumah Sakit X Tahun 2015 - Aurelia, Anna; Pujiyanti, Eka (Jurnal Ekonomi Kesehatan Indonesia, 2017)
X Hospital is a Class C Hospital in South Jakarta, which experiencing a substantial increased number of patients since the BPJS has implemented the referral system. Acute Coronary Syndrome (ACS) patient is a patient with a medical emergency require intensive treatment in the ICU. The purpose of this study was to analyze the cost for hospitalized ACS patients at X Hospital in 2015 using activity based costing. The study revealed that the unit cost of hospitalized ACS patients at X Hospital in 2015 was Rp 6.083.444,-. The Cost Recovery Rate for patients with fee-for-service was 227.98% and for BPJS patient was 71.38%. This study suggested the hospital to develop clinical pathway for ACS guidance, as well as recruiting full time doctors.